„Return to the Countryside” – a Qualitative Approach of Students’ Opinions About Rural Life - Dajnoki, Krisztina; Szabados, György Norbert; Kulcsár, Gergely; Kőmíves, Péter Miklós; Bácsné Bába, Éva (International Journal of Engineering and Management Sciences, 2018)
Nowadays, the research of rural areas’ specific features is one of the most interesting part of sociology. Within these studies the rural areas ability for survival and to retain forms an important basis. A pillar of these, that the youth from rural areas become sufficiently motivated to stay at or to return to their homeland and be able to redound development. We were looking for answers, that how university students, who participated in our current research are thinking about the hungarian countryside, in their opinion what are it’s advantages and disadvantages and it’s possible potentials. In addition, we examined those factors, which are contributing to that respondents who are studying in large cities want to stay there, but at the same time we wanted to explore the opposite factors, those that make tudents to return to the countryside. Last, but not least we investigated a very interesting topic, the relations between the respondents and the rural elite.